The Effect of Audit Tenure, Company Growth, and Leverage on Audit Fees - Pradita Widi Aryani; Ni Nyoman Alit Triani (Golden Ratio of Auditing Research, 2027)
This study examines the effects of audit tenure, company growth, and leverage on audit fees, with firm size and profitability included as control variables. The population consists of infrastructure companies listed on the Indonesia Stock Exchange during 2020–2024. Using purposive sampling, 45 firms were selected, resulting in 225 firm-year observations. Panel data regression analysis was employed, with the Random Effects Model (REM) identified as the most appropriate estimation method. The results indicate that audit tenure and company growth do not significantly affect audit fees. In contrast, leverage has a positive effect on audit fees, suggesting that higher financial risk increases audit effort and pricing. Among the control variables, firm size is not associated with audit fees, while profitability has a significant positive influence, indicating that more profitable firms tend to demand greater audit assurance. Simultaneously, all variables significantly affect audit fees. The model explains a limited proportion of audit fee variation, implying that other determinants remain influential. This study contributes to the audit pricing literature by providing empirical evidence from Indonesia’s infrastructure sector and highlighting the importance of leverage and profitability in audit fee determination. The findings offer practical insights for corporate management, auditors, and regulators in evaluating audit pricing and risk considerations. However, the study is limited to a single industry sector and a restricted set of variables. Future research should incorporate corporate governance, audit quality, auditor reputation, and industry specific factors to improve explanatory power.